Cantilever Supported Fiber Bragg Grating Flow Sensor for Space Applications - Perikala M.; Pathi V.V.L.; Rajan L.S.; Pandey P.C. (My University, 2025)
In this article we report design, mathematical formulation, simulation and fabrication of fiber optic flow sensor using fiber Bragg gratings (FBG) mounted on a cantilever-based transducer support. Design, fabrication and material parameters are optimized in a way that the sensor is operational even at higher flow velocities and finds potentially capable of determining flow rate in rocket fuel tanks for space applications. The reported cantilever supported FBG flow sensor based on simulation results has shown sensitivity to flow rates ranging from 0.1 m/s to as high as 10 m/s flow velocities with varied fuels ranging from liquid hydrogen with density 70.99 kg/m3 to Dinitrogen tetroxide with density 1110 kg/m3. Effect of flow rate is simulated and experimented by placing different weights on the disc and the wavelength shift corresponding to the weights from the designed sensor are recorded. It is observed that the experimental results matched with simulation results to around 50-60%. Flow sensor fabricated is thermally, electrically stable and with its minimal weight finds its extensive use in space applications. © 2020 IEEE.